2020
DOI: 10.31590/ejosat.642676
|View full text |Cite
|
Sign up to set email alerts
|

Yıkanmış Türk Linyit Kömürlerinin Üst Isıl Değerinin Destek Vektör Regresyonu ile Tahmini

Abstract: Öz Bu çalışmada yıkanmış Türk linyit kömürlerinin üst ısıl değeri (GCV), makine öğrenmesi yöntemleri ile kömür numunelerinin kuru baz kısa analiz sonuçları kullanılarak tahmin edilmiştir. Laboratuvar kömür analiz sonuçlarından elde edilen kül (A), uçucu madde (VM), kükürt (S) ve GCV değişkenleri kullanılarak veri kümesi oluşturulmuştur. Veri kümesine, Destek Vektör Regresyonu (SVR) ile Çok Katmanlı Algılayıcı (MLP), Genel Regresyon Sinir Ağı (GRNN) ve Radyal Temelli Fonksiyon Sinir Ağı (RBFN) olmak üzere üç fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Predictive models are compared to performance measurements. For GCV estimation, all models indicate that the SVR-based model is better than ANN-based models and THE RBFN-based model performs better than MLP and GRNN-based models [9].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Predictive models are compared to performance measurements. For GCV estimation, all models indicate that the SVR-based model is better than ANN-based models and THE RBFN-based model performs better than MLP and GRNN-based models [9].…”
Section: Introductionmentioning
confidence: 97%
“…It has been concluded that CO2 emissions have travelled on a yacht over the years [8]. Açıkkar et al (2020) the upper thermal value of Turkish lignite charcoal washed in its work (GCV) was estimated using machine learning methods and dry basic short analysis results of coal samples. In addition, they implemented three different Artificial Neural Networks (ANN) in their work, including Support Vector Regression (SVR) and Multilayer Sensor (MLP), General Regression Neural Network (GRNN), and radiant-based function Neural Network (RBFN), and GCV estimation models.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to reduce SO2 at its source before releasing it into the atmosphere (Acar et al, 2018). Low-quality coals are used by passing through certain stages to minimize environmental damage and because they are not suitable for direct use (Açıkkar and Sivrikaya, 2020). Since coals in our country are generally lignite coal with low calorific value, their evaluation for electricity generation purposes is more appropriate.…”
Section: Introductionmentioning
confidence: 99%